Factor Associated with Orthostatic Hypotension in Parkinson’s Disease - Selly Marisdina; Rini Nindela; Muhammad Hasnawi Haddani; Minda Nur'aini; Nurlia Puspita Ratnasari (AKSONA, 2025)
Highlight: Neurogenic orthostatic hypotension is commonly found in Parkinson’s disease (PD) and unnoticed by both patients and clinicians. Underweight has been associated to orthostatic hypotension in Parkinson’s disease, among other factors.   ABSTRACT Introduction: Orthostatic hypotension (OH) affect approximately 30% of patients with Parkinson's disease (PD). This condition not only reduces quality of life  but is also associated with increased mortality. OH has been shown to double the risk of falls in the elderly, worsens motor function, and  accelerate cognitive decline. There has been limited study into the prevalence and contributing factors of OH in Parkinson’s disease patients in Indonesia. Objective: This study aimed to determine factors associated with OH in patients with Parkinson’s disease. The variables analyzed included age, sex, duration of PD, disease stage based on the Hoehn and Yahr scale, levodopa equivalent dose (LED), the length of antiparkinsonian agents use, MoCA Ina (Montreal Cognitive Assessment Indonesian version) score, comorbid conditions, use of antihypertensive agents, and body mass index (BMI). Methods: This is a descriptive-analytic study with a cross-sectional design. The study population consisted of all Parkinson’s disease patients who visited the neurology polyclinics at  two hospitals in Palembang. Patients were selected based on specific inclusion and exclusion criteria. To discover associations, bivariate and multivariate analyses were performed. Results: The study involved 41 patients with PD at Mohammad Hoesin Hospital and Pusri Medika Hospital in Palembang, from June to December 2024. OH, was found in 43.9% of PD patients, most of whom reported symptoms. Bivariate and multivariate analyses revealed no significant associations between OH and factors such as comorbidities, the length of antiparkinsonian medication use, total LED, age, sex, duration of PD, disease stage (Hoehn and Yahr scale), and of the use of antihypertensive agents. However, underweight BMI was significantly associated with OH in PD patients (p = 0.002, OR = 34.571, 95% CI: 3.77–317.28). Conclusion:Underweight was identified as a significant associated factor for OH in PD patients.